Positively useless: irrelevant negative information enhances positive impressions1. Issue 2 (18th August 2016) - Shoham, Meyrav; Moldovan, Sarit; Steinhart, Yael
Abstract: This research examines the impact of irrelevant information and its valence (positive or negative) on consumers' evaluations, choices, and post‐choice satisfaction, within the context of online reviews. We demonstrate that seemingly irrelevant online reviews can enhance positive impressions, but only if they are labeled with a negative valence (e.g., with a one‐star rather than a five‐star rating). A series of studies provides support for this positive effect of negatively valenced irrelevant information; namely, the inclusion of a negatively valenced irrelevant review alongside positive reviews leads to greater product preferences, as consumers feel confident that the information they have about the product is more complete. We also demonstrate the moderating role of review source.